Upaya Pencegahan Stunting Melalui Pembentukan Masyarakat Sadar Gizi dan Mandiri Finansial - Thirafi, Luthfi; Akbarsyah, Nora; Fauzan, Farisadri (Farmers : Journal of Community Services, 2026)
Sukajaya Village, Pangandaran Regency, is still facing stunting. Various efforts have been made by the integrated health post, but many non-health factors also influence it, such as economic problems and residents who are trapped in pay-later debt. This condition continued until 2023 when 6 children were classified as stunted. This shows the need for other efforts outside of health materials to overcome this problem. The team surveyed the children of housewives in Sukajaya Village to measure their nutritional knowledge and the level of financial literacy of the local community. The results showed that knowledge of nutritional intake was quite good, but the level of financial literacy was still quite low. Based on these facts, the team designed a socialization activity for children's nutrition and basic financial literacy as well as the provision of complementary food assistance for children's nutritional intake which was carried out in Bulakgebang Hamlet. The activity was attended by around 35 mothers who were members of the integrated health post in Bulakgebang Hamlet. Participants now understand the importance of children's nutritional intake and the importance of having priorities in financial management.